2020
DOI: 10.1097/wad.0000000000000407
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Incidence in the Elderly Population of Greece

Abstract: Objectives: Recently a declining trend in dementia incidence rates has been reported in high-income countries. We investigated dementia incidence in a representative sample of the Greek population in the age group of 65 years and above. Methods: This research is part of the Hellenic Epidemiological Longitudinal Investigation of Aging and Diet (HELIAD). The incidence cohort consisted of 1072 participants who were reevaluated after a mean period of 3.09 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The detailed information gathered by all participants allowed us to adjust for many potential confounders, including age and sex, that have been shown to be important risk factors for AD/MCI development. 71,72 The reported association of CR and PRS in continuous form and not only in binary form, with AD/aMCI risk, adds to the generalizability and the practicability of our findings since they become more useful for other populations and cohorts. In other words, the analyses presented here demonstrated that associations were significant on a continuous scale and throughout the whole CR range (for each oneunit standard deviation increase of PRS and for each 1-year increase of CR) and not only under a rather cohort-specific threshold of PRS and CR.…”
Section: Incident Ad or Amci (%) Hr (95% Ci) Pmentioning
confidence: 66%
See 3 more Smart Citations
“…The detailed information gathered by all participants allowed us to adjust for many potential confounders, including age and sex, that have been shown to be important risk factors for AD/MCI development. 71,72 The reported association of CR and PRS in continuous form and not only in binary form, with AD/aMCI risk, adds to the generalizability and the practicability of our findings since they become more useful for other populations and cohorts. In other words, the analyses presented here demonstrated that associations were significant on a continuous scale and throughout the whole CR range (for each oneunit standard deviation increase of PRS and for each 1-year increase of CR) and not only under a rather cohort-specific threshold of PRS and CR.…”
Section: Incident Ad or Amci (%) Hr (95% Ci) Pmentioning
confidence: 66%
“…To help reduce reverse causality issues, we restricted our analyses to individuals not diagnosed with AD/aMCI at baseline. The detailed information gathered by all participants allowed us to adjust for many potential confounders, including age and sex, that have been shown to be important risk factors for AD/MCI development 71,72 . The reported association of CR and PRS in continuous form and not only in binary form, with AD/aMCI risk, adds to the generalizability and the practicability of our findings since they become more useful for other populations and cohorts.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Participants’ caregivers were involved in providing information whenever needed. Extensive details of the study design and data collection have been published previously [ 20 , 21 , 22 , 23 , 24 , 25 ]. Based on participants’ preferences, sessions were carried out at day-care centers for older adults, the participants’ homes, or municipal public health clinics.…”
Section: Methodsmentioning
confidence: 99%